Preparation method of 430SS stainless steel welding material
By performing multi-step process processing on 430SS stainless steel to prepare welding materials, the problem of insufficient corrosion resistance of the welding materials in high temperature and corrosion environments is solved, and the stability and corrosion resistance of the welding site are achieved.
Patent Information
- Application Number
- CN202411311356.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-04-11
AI Technical Summary
In spent fuel dry post-treatment technology, the reaction vessel used for electrolytic refining needs to withstand corrosion from coupling conditions such as high temperature and molten chloride salt, which makes it difficult for welding materials to meet the requirements of high temperature and corrosion environment.
A 430SS stainless steel welding material is used to prepare a method, including melting the substrate in a vacuum induction furnace to obtain a steel ingot, and then heating, forging, hot rolling processing, heat treatment and cold drawing processes to regulate the structural structure and grain size of the welding material, reduce impurity content, and improve the cleanliness and corrosion resistance of the welding material.
The 430SS stainless steel welding material prepared by this method can maintain stability in high temperature and in corrosion environments such as chloride molten salts. It is suitable for welding of reaction vessels, ensuring its corrosion resistance and working stability in long-term use.
Smart Images

Figure CN119794656A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of metal material welding, and in particular to a method for preparing 430SS stainless steel welding material. Background Art
[0002] Spent fuel dry reprocessing technology is a key link in the integrated closed-cycle nuclear energy system. The reaction vessels used for electrolytic refining need to withstand long-term corrosion from coupled working conditions such as high temperature and chloride molten salt, which brings huge challenges to the reaction vessels.
[0003] 430SS stainless steel has excellent high-temperature mechanical properties and high-temperature oxidation resistance, and can be used as a manufacturing material for reaction vessels. Therefore, in order to realize 430SS stainless steel as a structural material for reaction vessels, matching welding materials are required for welding to ensure the manufacturing and forming of the reaction vessels. Summary of the invention
[0004] In view of this, the embodiments of the present application hope to provide a method for preparing a welding material capable of welding 430SS stainless steel.
[0005] In order to achieve the above-mentioned purpose, the technical solution of the embodiment of the present application is implemented as follows:
[0006] The present application embodiment discloses a method for preparing a 430SS stainless steel welding material, the preparation method comprising:
[0007] placing a substrate in a vacuum induction furnace for smelting to obtain a steel ingot, wherein the chemical composition of the substrate includes carbon, silicon, titanium, aluminum, chromium, molybdenum, boron, nitrogen and iron;
[0008] Heating and forging the steel ingot to obtain a square bar;
[0009] Hot rolling the square bar to obtain a wire rod;
[0010] After the wire rod is subjected to a heat treatment process, the wire rod is subjected to a cold drawing process to obtain a welding material.
[0011] In one embodiment, the weight percentage of the carbon element is between 0.03% and 0.05%, the weight percentage of the silicon element is between 1.8% and 2.5%, the weight percentage of the titanium element is between 0.25% and 0.4%, the weight percentage of the aluminum element is not more than 0.4%, the weight percentage of the chromium element is between 16% and 18%, the weight percentage of the molybdenum element is between 0.35% and 0.5%, the weight percentage of the boron element is between 0.003% and 0.004%, the weight percentage of the nitrogen element is less than 0.04%, and the balance is iron element.
[0012] In one embodiment, the weight percentage of the aluminum element is less than 0.05%; or,
[0013] The weight percentage of the aluminum element is between 0.25% and 0.4.
[0014] In one embodiment, the step of heating and forging the steel ingot to obtain a square bar comprises:
[0015] The steel ingot is placed in a heating furnace for heating, wherein the heating temperature is between 1100° C. and 1150° C., and the holding time is 3 hours;
[0016] After being evenly heat-insulated, the steel ingot is forged, and then forged into the square rod by two-fire forging through drawing and roughening.
[0017] In one embodiment, the holding temperature of the hot rolling process is between 1100° C. and 1150° C., the holding time of the hot rolling process is between 1 h and 1.5 h, and the wire rod is formed by hot continuous rolling.
[0018] In one embodiment, the temperature of the heat treatment process is between 780° C. and 900° C., and the insulation time of the heat treatment process is between 10 min and 80 min.
[0019] In one embodiment, the cold drawing process includes:
[0020] Firstly, the wire rod is surface-grinded and coated with a coating agent, then single-pass cold drawing, vacuum annealing and continuous cold drawing are performed, and finally the wire is wound around a coil to obtain the welding material.
[0021] In one embodiment, the temperature of the vacuum annealing is between 780° C. and 900° C., and the time of the vacuum annealing is between 10 min and 80 min.
[0022] In one embodiment, the impurities in the welding material include sulfur and phosphorus, the weight percentage of the sulfur is less than 0.001%, and the weight percentage of the phosphorus is not more than 0.003%.
[0023] In one embodiment, the tensile yield strength of the welding material is between 370 MPa and 480 MPa, the tensile strength of the welding material is between 530 MPa and 690 MPa, and the elongation of the welding material is between 26% and 43%.
[0024] The embodiment of the present application discloses a method for preparing a 430SS stainless steel welding material. By placing a substrate in a vacuum induction furnace for smelting to obtain a steel ingot, the precipitate of carbide can be melted back into the substrate to improve the homogenization of the subsequent welding material, wherein the carbon element in the substrate can be strengthened by solid solution to increase the structural strength of the welding material; silicon is a deoxidizer in the steelmaking process, and its content is inevitable; titanium can inhibit intergranular corrosion of the welding material; aluminum can improve the oxidation resistance and corrosion resistance of the welding material by generating an oxide film; chromium is a ferrite-forming element, which can improve the corrosion resistance of the welding material and the nitrogen solubility in stainless steel, further improving the structural strength of the welding material; molybdenum can resist chloride ion corrosion to adapt to the corrosive environment of chloride molten salt; boron can improve the grain boundary strength of the welding material and reduce the occurrence of failure of the welding material's radiation resistance; nitrogen can improve the strength and toughness of the welding material. After smelting to obtain the steel ingot, the steel ingot can be heated and forged to obtain a square bar, and then the square bar can be hot-rolled to obtain a wire rod, and then the wire rod is subjected to a heat treatment process, and finally the heat-treated wire rod is subjected to a cold drawing process to obtain the welding material. In this way, the organizational structure and grain size of the subsequently formed welding material can be regulated, and the impurities in the welding material can be reduced to improve the cleanliness of the welding material. In this way, after welding the reaction vessel of the electrolytic refining, the welding point of the reaction vessel can adapt to the corrosion of coupled working conditions such as high temperature and chloride molten salt, and has good working stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic flow chart of a method for preparing a 430SS stainless steel welding material provided in an embodiment of the present application. DETAILED DESCRIPTION
[0026] It should be noted that, in the absence of conflict, the embodiments and technical features in the embodiments of the present application can be combined with each other, and the detailed description in the specific implementation method should be understood as an explanation of the purpose of the present application and should not be regarded as an improper limitation on the present application.
[0027] The present application will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] This application embodiment provides a method for preparing 430SS stainless steel welding material, please refer to Figure 1 , the preparation method comprises:
[0029] S1. placing a substrate in a vacuum induction furnace for smelting to obtain a steel ingot, wherein the chemical composition of the substrate includes carbon, silicon, titanium, aluminum, chromium, molybdenum, boron, nitrogen and iron;
[0030] S2, heating and forging the steel ingot to obtain a square bar;
[0031] S3, hot rolling the square bar to obtain a wire rod;
[0032] S4. After the wire rod is subjected to a heat treatment process, the wire rod is subjected to a cold drawing process to obtain welding material.
[0033] The preparation method of 430SS stainless steel welding material provided in the embodiment of the present application is to place the substrate in a vacuum induction furnace for smelting to obtain a steel ingot, and the precipitate of carbide can be melted back into the substrate to improve the homogenization of the subsequent welding material, wherein the carbon element in the substrate can be strengthened by solid solution to increase the structural strength of the welding material; silicon is a deoxidizer in the steelmaking process, and its content is inevitable; titanium element can inhibit intergranular corrosion of the welding material; aluminum element can improve the oxidation resistance and corrosion resistance of the welding material by generating an oxide film; chromium element is a ferrite-forming element, which can improve the corrosion resistance of the welding material and the nitrogen solubility in stainless steel, and further improve the structural strength of the welding material; molybdenum element can resist chloride ion corrosion to adapt to the corrosive environment of chloride molten salt; boron element can improve the grain boundary strength of the welding material and reduce the occurrence of failure of the radiation resistance of the welding material; nitrogen element can improve the strength and toughness of the welding material. After smelting to obtain the steel ingot, the steel ingot can be heated and forged to obtain a square bar, and then the square bar can be hot-rolled to obtain a wire rod, and then the wire rod is subjected to a heat treatment process, and finally the heat-treated wire rod is subjected to a cold drawing process to obtain the welding material. In this way, the organizational structure and grain size of the subsequently formed welding material can be regulated, and the impurities in the welding material can be reduced to improve the cleanliness of the welding material. In this way, after welding the reaction vessel of the electrolytic refining, the welding point of the reaction vessel can adapt to the corrosion of coupled working conditions such as high temperature and chloride molten salt, and has good working stability.
[0034] Exemplarily, in one embodiment, the size of the square rod may be 45 mm×45 mm.
[0035] In one embodiment, the weight percentage of carbon element is between 0.03% and 0.05%, the weight percentage of silicon element is between 1.8% and 2.5%, the weight percentage of titanium element is between 0.25% and 0.4%, the weight percentage of aluminum element is not more than 0.4%, the weight percentage of chromium element is between 16% and 18%, the weight percentage of molybdenum element is between 0.35% and 0.5%, the weight percentage of boron element is between 0.003% and 0.004%, the weight percentage of nitrogen element is less than 0.04%, and the balance is iron element.
[0036] Exemplarily, the weight percentage of carbon element can be 0.03%, 0.035%, 0.04%, 0.045% or 0.05%, etc. In this way, by setting the appropriate weight percentage, not only can the situation where carbides precipitate from austenite grain boundaries due to excessive carbon content, resulting in intergranular corrosion and reduced mechanical properties, be reduced, but also better welding with 430SS stainless steel can be achieved.
[0037] The weight percentage of silicon element can be 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4% or 2.5%, etc.
[0038] The weight percentage of titanium element can be 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39% or 0.4%, etc. In this way, by setting the appropriate weight percentage of titanium element, not only the welding performance can be improved, but also the intergranular corrosion of subsequent welding materials can be effectively inhibited, thereby improving the corrosion resistance of the welding materials.
[0039] The weight percentage of aluminum element is not more than 0.4%. Thus, by setting a suitable weight percentage of aluminum element, the oxidation resistance and corrosion resistance of the welding material can be improved.
[0040] The weight percentage of chromium can be 16%, 16.5%, 17% or 18%, etc. In this way, by setting the appropriate weight percentage of chromium, not only the corrosion resistance of the welding material can be improved, but also the increase of ferrite can be reduced, thereby reducing the precipitation of harmful phases and improving the homogeneity of the welding material.
[0041] The weight percentage of the molybdenum element can be 0.35%, 0.4%, 0.45% or 0.5%, etc. Here, since the molybdenum element is a ferrite-forming element, by setting the appropriate weight percentage of the molybdenum element, not only the pitting corrosion resistance of the welding material can be improved, but also the increase of ferrite can be reduced, thereby reducing the precipitation of harmful phases and improving the homogeneity of the welding material.
[0042] The weight percentage of boron can be 0.003%, 0.0035% or 0.004%. Thus, by setting a suitable weight percentage of boron, not only the grain boundary strength of the welding material can be improved, but also the failure of the welding material's radiation resistance can be reduced.
[0043] The weight percentage of nitrogen can be 0.035%, 0.03%, 0.025%, 0.02%, 0.015% or 0.01%, etc. In this way, by setting a suitable weight percentage of nitrogen, not only the structural strength of the welding material can be improved, but also the corrosion resistance of the welding material can be reduced significantly.
[0044] Iron is the base element of welding wire.
[0045] It should be noted that during welding, high temperature will reduce the content of some elements. If the content of each element in the welding material does not match the content of the main body, welding may fail.
[0046] In one embodiment, the weight percentage of aluminum is less than 0.04%. For example, the weight percentage of aluminum can be 0.035%, 0.03%, 0.025%, 0.02%, 0.015% or 0.01%, etc. In this way, the aluminum element can be set to a suitable weight percentage, which can reduce the situation where grain coarsening causes a decrease in homogeneity.
[0047] In one embodiment, the weight percentage of aluminum is between 0.25% and 0.4. For example, the weight percentage of aluminum can be 0.25%, 0.3%, 0.35% or 0.4%, etc. Thus, by setting a suitable weight percentage of aluminum, the thickness of the oxide film can be increased, thereby improving the anti-oxidation and corrosion resistance.
[0048] In one embodiment, S2, the step of heating and forging the steel ingot to obtain a square bar, comprises:
[0049] S21, placing the steel ingot in a heating furnace for heating, wherein the heating temperature is between 1100° C. and 1150° C., and the holding time is 3 hours;
[0050] S22. After the heat preservation is uniform, the steel ingot is forged, and then forged into the square rod by two-fire forging through drawing and roughening.
[0051] Exemplarily, the steel ingot is placed in a heating furnace for heating, and the heating temperature can be 1100°C, 1110°C, 1120°C, 1130°C, 1140°C or 1150°C, etc., and the insulation time can be 3 hours. In this way, after uniform insulation, that is, after the temperature of various parts on the steel ingot is roughly the same, it can be forged. Through multiple lengthening and roughening, as well as quenching and tempering, it can be forged into a square rod. In this way, the mechanical properties of subsequent welding materials can be improved.
[0052] In one embodiment, the holding temperature of the hot rolling process is between 1100° C. and 1150° C., the holding time of the hot rolling process is between 1 h and 1.5 h, and the hot rolling is performed into a wire rod.
[0053] Exemplarily, the holding temperature of hot rolling can be 1100°C, 1110°C, 1120°C, 1130°C, 1140°C or 1150°C, etc. The holding time of hot rolling can be 1h, 1.1h, 1.2h, 1.3h, 1.4h or 1.5h, etc., and finally the square bar can be rolled into a wire rod by a hot rolling mill. In this way, on the one hand, the square bar can be easily rolled into a required shape and size after hot rolling, with strong processing flexibility and high production efficiency; on the other hand, the hot rolling process can refine the grains inside the metal, make the surface oxidation of the wire rod obvious, the oxide scale becomes loose, and there are no defects such as cracks, folds and scars, so that the strength, toughness and ductility of subsequent welding materials can be improved.
[0054] In one embodiment, the diameter of the wire rod can be 8.5 mm, so that it is convenient to draw it into welding wire.
[0055] In one embodiment, the temperature of the heat treatment process is between 780° C. and 900° C., and the holding time of the heat treatment process is between 10 min and 80 min.
[0056] For example, the temperature of the heat treatment process may be 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C, etc. The holding time of the heat treatment process may be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min or 80 min, etc. In this way, by setting the appropriate temperature and holding time of the heat treatment process, not only the microstructure and grain size of the metal can be regulated, but also the precipitates of carbides can be melted back into the matrix to improve the homogenization of the welding material.
[0057] In one embodiment, the cold drawing process includes: firstly grinding the surface of the wire rod and applying a coating agent on the surface, then performing single-pass cold drawing, vacuum annealing and continuous cold drawing, and finally winding the wire into a coil to obtain the welding material.
[0058] For example, the surface of the wire rod can be polished first, so that not only can the surface attachments such as oxide scale be removed, but also the surface roughness can be improved, which is convenient for subsequent processing. By applying a film agent on the surface, on the one hand, a protective film can be formed on the surface of the wire rod to prevent moisture, oxygen and other corrosive media from contacting the matrix of the wire rod, thereby slowing down or preventing the occurrence of corrosion reactions; on the other hand, it can be used for subsequent cold drawing to reduce wear. Then a single-pass cold drawing can be used to draw the wire rod for the first time, so that the wire rod is roughly drawn into the required size and shape, and then it is vacuum annealed to improve the microstructure in the metal material, improve the ductility and toughness, and also discharge the impurities inside the metal to improve the cleanliness of the subsequent welding material. Finally, it can be drawn into the welding material of the required size by continuous cold drawing, and then collected around the disk, which can protect the welding material.
[0059] Exemplarily, in one embodiment, the shape of the welding material can be strip or wire.
[0060] In one embodiment, the temperature of vacuum annealing is between 780° C. and 900° C., and the time of vacuum annealing is between 10 min and 80 min.
[0061] Exemplarily, in one embodiment, the temperature of vacuum annealing can be 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C, etc. The time of vacuum annealing can be 10min, 20min, 30min, 40min, 50min, 60min, 70min or 80min, etc. In this way, by setting the appropriate temperature and time of vacuum annealing, the tensile properties of the metal can be effectively improved, and the impurities in the metal can be significantly reduced, and the cleanliness is high.
[0062] In one embodiment, the impurities in the welding material include sulfur and phosphorus, the weight percentage of sulfur is less than 0.001%, and the weight percentage of phosphorus is not more than 0.003%.
[0063] In this way, the toughness of the welding material can be improved and the thermal cracking of the welding material can be reduced, so that the welding material can adapt to the high-temperature electrolytic refining environment.
[0064] In one embodiment, the tensile yield strength of the welding material is between 370 MPa and 480 MPa, the tensile strength of the welding material is between 530 MPa and 690 MPa, and the elongation of the welding material is between 26% and 43%.
[0065] In this way, the tensile properties of the weld can be improved to meet subsequent welding requirements.
[0066] It should be noted that the chemical composition and corresponding weight percentage of the substrate are substantially the same as the chemical composition and corresponding weight percentage of the prepared welding material.
[0067] Exemplarily, in one embodiment, the chemical components of the substrate and the corresponding weight percentages are: carbon: 0.038%; silicon: 2.2%; titanium: 0.29%; aluminum: 0.02%; chromium: 16.96%; molybdenum: 0.42%; boron: 0.0034%; nitrogen: 0.016%; the balance is iron. The substrate is first placed in a vacuum induction furnace for smelting to prepare a steel ingot. The steel ingot can be forged in a heating furnace at any temperature between 1100°C and 1150°C for 3 hours, and then forged, stretched and roughened, and forged into a square bar with a size of 45mm×45mm. The square bars are hot rolled, and the holding temperature of the hot rolling process is kept at any temperature between 1100℃ and 1150℃ for 1h to 1.5h, and hot rolled to a wire rod with a final diameter of 8.5mm; the surface oxidation of the wire rod is obvious, the oxide scale is relatively loose, and there are no defects such as cracks, folds and scars. Then the heat treatment process of the wire rod is carried out, and the heat treatment process is: keep warm at a temperature of 850℃ for 15min. Then the wire rod is further processed by the cold drawing process, and the process includes: surface grinding, surface coating agent, single-pass cold drawing, vacuum annealing (temperature is 850℃, holding time is 15min), continuous cold drawing, winding and coiling, and finally the finished welding wire is obtained. The impurity content of the welding wire is: sulfur element is less than 0.001%, and phosphorus element is less than 0.003%. Then, the prepared welding wire was subjected to a room temperature tensile performance test according to GB / T 228.8-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method", and the results showed that its tensile yield strength was 461 MPa, the tensile strength was 658 MPa, and the elongation was 33%.
[0068] Exemplarily, in one embodiment, the chemical components of the substrate and the corresponding weight percentages are: carbon: 0.038%; silicon: 2.2%; titanium: 0.29%; aluminum: 0.02%; chromium: 16.96%; molybdenum: 0.42%; boron: 0.0034%; nitrogen: 0.016%; the balance is iron. The substrate is first placed in a vacuum induction furnace for smelting to prepare a steel ingot. The steel ingot can be forged in a heating furnace at any temperature between 1100°C and 1150°C for 3 hours, and then forged, stretched and roughened, and forged into a square bar with a size of 45mm×45mm. The square rod is hot-rolled, and the holding temperature of the hot rolling process is kept at any temperature between 1100℃ and 1150℃ for 1h to 1.5h, and hot-rolled to a wire rod with a final diameter of 8.5mm; the surface oxidation of the wire rod is obvious, the oxide scale is relatively loose, and there are no defects such as cracks, folds and scars. Then the heat treatment process of the wire rod is carried out, and the heat treatment process is: keep warm at a temperature of 850℃ for 30min. Then the wire rod is further processed by the cold drawing process, and the process includes: surface grinding, surface coating agent, single-pass cold drawing, vacuum annealing (temperature is 850℃, holding time is 30min), continuous cold drawing, winding and coiling, and finally the finished welding wire is obtained. The impurity content of the welding wire is: sulfur element is less than 0.001%, and phosphorus element is less than 0.003%. Then, the prepared welding wire was subjected to a room temperature tensile performance test according to GB / T 228.8-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method", and the results showed that its tensile yield strength was 445 MPa, the tensile strength was 638 MPa, and the elongation was 35%.
[0069] Exemplarily, in one embodiment, the chemical components of the substrate and the corresponding weight percentages are: carbon: 0.038%; silicon: 2.2%; titanium: 0.29%; aluminum: 0.02%; chromium: 16.96%; molybdenum: 0.42%; boron: 0.0034%; nitrogen: 0.016%; the balance is iron. The substrate is first placed in a vacuum induction furnace for smelting to prepare a steel ingot. The steel ingot can be forged in a heating furnace at any temperature between 1100°C and 1150°C for 3 hours, and then forged, stretched and roughened, and forged into a square bar with a size of 45mm×45mm. The square rod is hot-rolled, and the holding temperature of the hot rolling process is kept at any temperature between 1100℃ and 1150℃ for 1h to 1.5h, and hot-rolled to a wire rod with a final diameter of 8.5mm; the surface oxidation of the wire rod is obvious, the oxide scale is relatively loose, and there are no defects such as cracks, folds and scars. Then the heat treatment process of the wire rod is carried out, and the heat treatment process is: keep warm at a temperature of 850℃ for 60min. Then the wire rod is further processed by the cold drawing process, and the process includes: surface grinding, surface coating agent, single-pass cold drawing, vacuum annealing (temperature is 850℃, holding time is 60min), continuous cold drawing, winding and coiling, and finally the finished welding wire is obtained. The impurity content of the welding wire is: sulfur element is less than 0.001%, and phosphorus element is less than 0.003%. Then, the prepared welding wire was subjected to a room temperature tensile performance test according to GB / T 228.8-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method", and the results showed that its tensile yield strength was 446 MPa, the tensile strength was 627 MPa, and the elongation was 37%.
[0070] Exemplarily, in one embodiment, the chemical components of the substrate and the corresponding weight percentages are: carbon: 0.037%; silicon: 2.21%; titanium: 0.29%; aluminum: 0.31%; chromium: 16.91%; molybdenum: 0.41%; boron: 0.0033%; nitrogen: 0.018%; the balance is iron. The substrate is first placed in a vacuum induction furnace for smelting to prepare a steel ingot. The steel ingot can be forged in a heating furnace at any temperature between 1100°C and 1150°C for 3 hours, and then forged, stretched and roughened, and forged into a square bar with a size of 45mm×45mm. The square bars are hot rolled, and the holding temperature of the hot rolling process is kept at any temperature between 1100℃ and 1150℃ for 1h to 1.5h, and hot rolled to a wire rod with a final diameter of 8.5mm; the surface oxidation of the wire rod is obvious, the oxide scale is relatively loose, and there are no defects such as cracks, folds and scars. Then the heat treatment process of the wire rod is carried out, and the heat treatment process is: keep warm at a temperature of 850℃ for 15min. Then the wire rod is further processed by the cold drawing process, and the process includes: surface grinding, surface coating agent, single-pass cold drawing, vacuum annealing (temperature is 850℃, holding time is 15min), continuous cold drawing, winding and coiling, and finally the finished welding wire is obtained. The impurity content of the welding wire is: sulfur element is less than 0.001%, and phosphorus element is less than 0.003%. Then, the prepared welding wire was subjected to a room temperature tensile performance test according to GB / T 228.8-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method", and the results showed that its tensile yield strength was 395 MPa, the tensile strength was 560 MPa, and the elongation was 36%.
[0071] Exemplarily, in one embodiment, the chemical components of the substrate and the corresponding weight percentages are: carbon: 0.037%; silicon: 2.21%; titanium: 0.29%; aluminum: 0.31%; chromium: 16.91%; molybdenum: 0.41%; boron: 0.0033%; nitrogen: 0.018%; the balance is iron. The substrate is first placed in a vacuum induction furnace for smelting to prepare a steel ingot. The steel ingot can be forged in a heating furnace at any temperature between 1100°C and 1150°C for 3 hours, and then forged, stretched and roughened, and forged into a square bar with a size of 45mm×45mm. The square rod is hot-rolled, and the holding temperature of the hot rolling process is kept at any temperature between 1100℃ and 1150℃ for 1h to 1.5h, and hot-rolled to a wire rod with a final diameter of 8.5mm; the surface oxidation of the wire rod is obvious, the oxide scale is relatively loose, and there are no defects such as cracks, folds and scars. Then the heat treatment process of the wire rod is carried out, and the heat treatment process is: keep warm at a temperature of 850℃ for 30min. Then the wire rod is further processed by the cold drawing process, and the process includes: surface grinding, surface coating agent, single-pass cold drawing, vacuum annealing (temperature is 850℃, holding time is 30min), continuous cold drawing, winding and coiling, and finally the finished welding wire is obtained. The impurity content of the welding wire is: sulfur element is less than 0.001%, and phosphorus element is less than 0.003%. Then, the prepared welding wire was subjected to a room temperature tensile performance test according to GB / T 228.8-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method", and the results showed that its tensile yield strength was 393 MPa, the tensile strength was 557 MPa, and the elongation was 38%.
[0072] Exemplarily, in one embodiment, the chemical components of the substrate and the corresponding weight percentages are: carbon: 0.037%; silicon: 2.21%; titanium: 0.29%; aluminum: 0.31%; chromium: 16.91%; molybdenum: 0.41%; boron: 0.0033%; nitrogen: 0.018%; the balance is iron. The substrate is first placed in a vacuum induction furnace for smelting to prepare a steel ingot. The steel ingot can be forged in a heating furnace at any temperature between 1100°C and 1150°C for 3 hours, and then forged, stretched and roughened, and forged into a square bar with a size of 45mm×45mm. The square rod is hot-rolled, and the holding temperature of the hot rolling process is kept at any temperature between 1100℃ and 1150℃ for 1h to 1.5h, and hot-rolled to a wire rod with a final diameter of 8.5mm; the surface oxidation of the wire rod is obvious, the oxide scale is relatively loose, and there are no defects such as cracks, folds and scars. Then the heat treatment process of the wire rod is carried out, and the heat treatment process is: keep warm at a temperature of 850℃ for 60min. Then the wire rod is further processed by the cold drawing process, and the process includes: surface grinding, surface coating agent, single-pass cold drawing, vacuum annealing (temperature is 850℃, holding time is 60min), continuous cold drawing, winding and coiling, and finally the finished welding wire is obtained. The impurity content of the welding wire is: sulfur element is less than 0.001%, and phosphorus element is less than 0.003%. Then, the prepared welding wire was subjected to a room temperature tensile performance test according to GB / T 228.8-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method", and the results showed that its tensile yield strength was 385 MPa, the tensile strength was 536 MPa, and the elongation was 32%.
[0073] The above is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. All modifications, equivalent substitutions, improvements, etc. within the spirit and principles of the present application are included in the protection scope of the present application.
Claims
1. A method for preparing 430SS stainless steel welding material, characterized in that: The preparation method comprises: placing a substrate in a vacuum induction furnace for smelting to obtain a steel ingot, wherein the chemical composition of the substrate includes carbon, silicon, titanium, aluminum, chromium, molybdenum, boron, nitrogen and iron; Heating and forging the steel ingot to obtain a square bar; Hot rolling the square bar to obtain a wire rod; After the wire rod is subjected to a heat treatment process, the wire rod is subjected to a cold drawing process to obtain a welding material.
2. The preparation method according to claim 1, characterized in that: The weight percentage of the carbon element is between 0.03% and 0.05%, the weight percentage of the silicon element is between 1.8% and 2.5%, the weight percentage of the titanium element is between 0.25% and 0.4%, the weight percentage of the aluminum element is not more than 0.4%, the weight percentage of the chromium element is between 16% and 18%, the weight percentage of the molybdenum element is between 0.35% and 0.5%, the weight percentage of the boron element is between 0.003% and 0.004%, the weight percentage of the nitrogen element is less than 0.04%, and the balance is iron element.
3. The preparation method according to claim 2, characterized in that: The weight percentage of the aluminum element is less than 0.05%; or, The weight percentage of the aluminum element is between 0.25% and 0.
4.
4. The preparation method according to claim 1, characterized in that: The step of heating and forging the steel ingot to obtain a square bar comprises: The steel ingot is placed in a heating furnace for heating, wherein the heating temperature is between 1100° C. and 1150° C., and the holding time is 3 hours; After being evenly heat-insulated, the steel ingot is forged, and then forged into the square rod by two-fire forging through drawing and roughening.
5. The preparation method according to claim 1, characterized in that: The holding temperature of the hot rolling process is between 1100° C. and 1150° C., the holding time of the hot rolling process is between 1 h and 1.5 h, and the wire rod is formed by hot continuous rolling.
6. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment process is between 780° C. and 900° C., and the insulation time of the heat treatment process is between 10 min and 80 min.
7. The preparation method according to claim 1, characterized in that: The cold drawing process comprises: Firstly, the wire rod is surface-grinded and coated with a coating agent, then single-pass cold drawing, vacuum annealing and continuous cold drawing are performed, and finally the wire is wound around a coil to obtain the welding material.
8. The preparation method according to claim 7, characterized in that: The temperature of the vacuum annealing is between 780° C. and 900° C., and the time of the vacuum annealing is between 10 min and 80 min.
9. The preparation method according to claim 1, characterized in that: The impurities in the welding material include sulfur and phosphorus. The weight percentage of the sulfur is less than 0.001%, and the weight percentage of the phosphorus is not more than 0.003%.
10. The preparation method according to claim 1, characterized in that: The tensile yield strength of the welding material is between 370MPa and 480MPa, the tensile strength of the welding material is between 530MPa and 690MPa, and the elongation of the welding material is between 26% and 43%.
Citation Information
Patent Citations
Welding wire molten steel for welding low-pressure hydrogen conveying pipeline, welding wire and preparation method of welding wire
CN116586819A
Austenitic stainless steel welding wire and preparation method thereof
CN118559281A
Method for manufacturing stainless steel welding wire
JP2007331022A
Recycled plastic bag using waste plastic and its manufacturing method
KR102804578B1
Nickel-base alloy for the electro-welding of nickel alloys and steels, welding wire and use
US20040062677A1